Rehabilitation of Maxillary defect using Removable Maxillary Cast Partial Denture Hollow Prosthesis for managing Mucomycosis patient: A Clinical Case Report - Jyoti Yadav; Shefali Singla; Virender Kumar; Lalit Kumar; Neha Verma (Journal of Indonesian Dental Association, 2023)
Introduction: Mucormycosis is the fungal infection which especially affects immunocompromised patients. Case Report: In this case report, prosthetic rehabilitation of maxillary defect due to past mucormycosis in an uncontrolled diabetic patient was discussed by means of lightweight prosthesis by attaching a hollow occlusal shim to cast partial denture framework as absence of alveolar ridge on the defect side tends to increase the weight of the prosthesis which would have compromised the retention of the prosthesis. Conclusion: This technique is simple, economical and less time-consuming.